Mice Deficient in Cryptochrome 1 (Cry1−/−) Exhibit Resistance to Obesity Induced by a High-Fat Diet - Griebel, Guy; Ravinet-Trillou, Christine; Beeské, Sandra; Avenet, Patrick; Pichat, Philippe (Frontiers in Endocrinology, 2014)
Disruption of circadian clock enhances the risk of metabolic syndrome, obesity, and type 2 diabetes. Circadian clocks rely on a highly regulated network of transcriptional and translational loops that drive clock-controlled gene expression. Among these transcribed clock genes are cryptochrome (CRY) family members, which comprise Cry1 and Cry2. While the metabolic effects of deletion of several core components of the clock gene machinery have been well characterized, those of selective inactivation of Cry1 or Cry2 genes have not been described. In this study we demonstrate that ablation of Cry1, but not Cry2, prevents high-fat diet (HFD)-induced obesity in mice. Despite similar caloric intake, Cry1-/- mice on HFD gained markedly less weight (-18 %) at the end of the 16-week experiment) and displayed reduced fat accumulation compared to wild-type (WT) littermates (-61 %), suggesting increased energy expenditure. Analysis of serum lipid and glucose profiles showed no difference between Cry1-/- and WT mice. Both Cry1-/- and Cry2-/- mice are indistinguishable from WT controls in body weight, fat and protein contents, and food consumption when they are allowed unlimited access to a standard rodent diet. We conclude that although CRY signaling may not be essential for the maintenance of energy homeostasis under steady-state nutritional conditions, Cry1 may play a role in readjusting energy balance under changing nutritional circumstances. These studies reinforce the important role of circadian clock genes in energy homeostasis and suggest that Cry1 is a plausible target for antiobesity therapy.